2001
DOI: 10.1042/cs20000252
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery hypertrophy occurs in coronary atherosclerosis and is independent of blood pressure

Abstract: Endothelial dysfunction, believed to underlie the structural changes of atherosclerosis, is a systemic phenomenon. Despite this, the radial artery has been considered as devoid of atherosclerosis and is commonly used as a conduit in coronary artery bypass grafting (CABG). Recently, histological study has shown intimal hyperplasia and other structural changes consistent with early atherosclerosis in the radial artery. The objective of the present study was to determine if structural changes in the radial artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
2
9
0
1
Order By: Relevance
“…12 Although the media-to-lumen ratio increases, the medial cross-sectional area remains unchanged, resulting in a decrease in the inner diameter of the vessel. 12,13 In our study we found that there was a strong negative correlation between the inner diameters of RRAs and the increase of risk factor scores. It meant that the increase of the risk factor numbers were correlated with the decrease of the inner diameters of RRAs.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…12 Although the media-to-lumen ratio increases, the medial cross-sectional area remains unchanged, resulting in a decrease in the inner diameter of the vessel. 12,13 In our study we found that there was a strong negative correlation between the inner diameters of RRAs and the increase of risk factor scores. It meant that the increase of the risk factor numbers were correlated with the decrease of the inner diameters of RRAs.…”
Section: Discussionsupporting
confidence: 51%
“…Mourad et al 17 previously reported that the compliance of radial arteries in hypertensive patients was not significantly different from those with normotension, despite increased wall thickness in the hypertensive patients. Mackay et al 13 assumed that radial artery intima-media hypertrophy was likely to be independent of blood pressure effects, and it was suspected due to endothelial dysfunction. Loh et al 18 found that risk factors that positively affected the size of the radial artery were sex, hypertension, and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the RA may be vulnerable to atherosclerosis. In fact, atherosclerotic change is more prevalent in the RA (5% to 10% incidence) than in the ITA (<1%) at the time of surgery 48‐51,53,63‐66 . Vascular wall morbidity is exacerbated in patients with diabetes mellitus or renal dysfunction 67,68 .…”
Section: Vascular Biological Characteristics Of the Ramentioning
confidence: 99%
“…Although the radial arteries (RAs) are not prone to atherosclerosis, it has been shown that RA hypertrophy occurs in patients with coronary atherosclerosis who are waiting for coronary bypass surgery (MacKay et al, 2001). Hitherto, detailed in vivo descriptions of RA morphology with separation of the tunica intima from underlying structures were not possible in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Although the radial arteries (RAs) are not prone to atherosclerosis, it has been shown that RA hypertrophy occurs in patients with coronary atherosclerosis who are waiting for coronary bypass surgery (MacKay et al. , 2001).…”
Section: Introductionmentioning
confidence: 99%